Off-line partial discharge measurement and localization for a 33/6.9 kV in-service transformer - Selva, A. M.; Azis, N.; Yousof, M. F. M.; Sallehuddin, N.; Tadam, A. B.; Saliang, A. D. (IEEE, 2022)
This paper presents an investigation on the off-line Partial Discharge (PD) and localization for 1 unit of in-service 5 MVA 33/6.9 kV oil immersed transformer. First, Dissolved Gas Analysis (DGA) was performed to confirm the existence of PD activities. Next, offline PD measurements were carried out on both LV and HV windings. Once the transformer has been energized, PD localization was performed at different sections of the transformer tank. It is found that HV windings are having possible multiples PD activities based on offline Phase-Resolved Partial Discharge (PRPD) pattern and PD localization.